2011
DOI: 10.1007/s00420-011-0634-7
|View full text |Cite
|
Sign up to set email alerts
|

Depression in the workplace: a systematic review of evidence-based prevention strategies

Abstract: The findings are quite sobering given the high prevalence of depression and the individual and societal burden caused by it. More tailor-made interventions in the workplace targeting depression directly are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 34 publications
2
19
0
2
Order By: Relevance
“…In order to prove a causal relationship and to show that improving work autonomy could in fact lower the burden of depressive symptoms, a controlled intervention trial aiming to improve well-being would be necessary. Since depression is a prominent health problem for young doctors, intervention studies are warranted (Dietrich et al 2011).…”
Section: Meaning Of the Studymentioning
confidence: 99%
“…In order to prove a causal relationship and to show that improving work autonomy could in fact lower the burden of depressive symptoms, a controlled intervention trial aiming to improve well-being would be necessary. Since depression is a prominent health problem for young doctors, intervention studies are warranted (Dietrich et al 2011).…”
Section: Meaning Of the Studymentioning
confidence: 99%
“…It has been suggested that depression can be effectively prevented and managed particularly in workplace settings where large populations can be reached 11. For a number of years, stress management programmes were considered as the most common strategy for mental health promotion in the workplace 12.…”
Section: Introductionmentioning
confidence: 99%
“…Another review identified 10 RCTs and 2 non-RCTs,15 but the authors concluded that only limited evidence can be drawn from these studies. There was also another review that focused solely on interventions that only targeted depression, but excluded any stress management interventions 11. Nevertheless, stress management interventions may decrease stress levels in addition to other mental health outcomes such as depression 13.…”
Section: Introductionmentioning
confidence: 99%
“…However, gaps of two sorts exist in this research. First, much of this research focused on depression [10,16-24] and little is known about the associations of other common mental disorders with employment outcomes. Second, this research has been mainly based on cross-sectional rather than longitudinal studies.…”
Section: Introductionmentioning
confidence: 99%